Study on sustainable recovery and extraction of polyhydroxyalkanoates (PHAs) produced by Cupriavidus necator using waste glycerol for medical applications - Gahlawat, Geeta (Array, 2019)
The current study shows that Cupriavidus necator has the ability to grow on waste glycerol as carbon source, and can synthesize a highly thermostable copolymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate). Batch cultivation on waste glycerol showed accumulation of 6.76 g L–1 biomass containing 4.84 g L–1 poly(3-hydroxybutyrate-co-3-hydroxyvalerate) copolymer with 3-hydroxyvalerate content of 24.6 mol%. A novel recovery strategy was developed for the extraction of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) copolymer from Cupriavidus necator using recyclable solvents, i.e., propylene carbonate, butyl acetate, isoamyl alcohol, and ethyl acetate. Propylene carbonate demonstrated the recovery efficiency of 90 % and polymer purity of 95 %, at 120 °C after 30 min. Ethyl acetate exhibited a higher efficiency than butyl acetate in terms of recovering the copolymer from cells. Ethyl acetate extraction demonstrated a recovery yield of 96 % and purity of 93 % at 100 °C. Efficacy of an anionic surfactant, linear alkylbenzene sulfonic acid (LAS), was also tested for extraction, and it showed maximum yield of 84 % and purity of 90 % at 80 °C and pH 5.0. Extraction of copolymer using these solvents could help in replacing generally used chlorinated toxic solvents, such as 1,2 dichloroethane and chloroform. Further, GPC, TGA and DSC analysis revealed that the thermo-physical properties were not significantly affected by the extraction method. However, the molecular weight distribution of the polymer showed a variation depending on the type of solvent used for extraction. Subsequently, endotoxins were removed efficiently to less than 5 EU g–1 of copolymer using alkali at optimized conditions of 6 h digestion time and 2.5 N NaOH concentration for medical applications.